MODERNIZATION OF FISHERY AND CONFLICT AMONG FISHERMEN IN BENGKALIS DISTRICT OF RIAU PROVINCE - Yasir Yasir; Nurjanah Nurjanah; Noor Efni Salam (Universitas Gadjah Mada, 2019)
Modernization fishery tools facilitated by government support is assumed to help improving fishermen incomes. However, on reality the introduction of the more advanced tools has also posed challenges to the traditional fishermen. Modernization of fishery technology can also caused conflict between fishermen. This found evidence in the conflict between longline (rawai) fishers and trawl fishers in Bengkalis District-Riau has occurred for more than 30 years. The modernization of fishing gear by government is one of the triggers of the conflict. This research aims to uncover the root causes of conflict and understand communication management to overcome the conflict between traditional and modern fishers. This research used the qualitative and explorative method. The results show that the conflict among fishers in the coastal area of Bengkalis occurs due to the use of trawl and the territorial dispute in fishing. The causes of conflict between fishers are related to lack of rule understanding, economic inequality, and differences in value and culture. Government delivery of the aid that is not sensitive to the need fo traditional fishermen play role in the conflict. This is due to the problem communication management. The resolution of the conflicts at the Fishers community level is possible if the government is able to build the atmosphere through appropriate policies, programs and communication ways for the Fishers community.